Community-based newborn care utilisation and associated factors in Geze Gofa rural district, South Ethiopia: a community-based cross-sectional study. Issue 8 (20th August 2020) - Gebremedhin, Tsegaye; Atnafu, Asmamaw; Dellie, Endalkachew
Abstract : Objective: The community-based newborn care (CBNC) is a newborn care package along the maternal and newborn health continuum of care that has been implemented at the community level in Ethiopia. The utilisation which might be affected by several factors has not been well assessed. Thus, this study aimed to examine the utilisation of CBNC and associated factors among women who delivered recently in Geze Gofa rural district, south Ethiopia. Design: Cross-sectional study. Setting: Community-based. Participants: Three-hundred seventy-one women who had their newborns recently were randomly selected. Then, they were interviewed at their places using an interviewer-administered structured questionnaire. Methods: A binary logistic regression analysis was done. In the multivariable logistic regression analysis, a p value of <0.05 and adjusted OR (AOR) with 95% CI were used to identify factors statistically associated with CBNC utilisation. Outcomes: CBNC utilisation. Results: The findings showed that the overall utilisation of CBNC by women who delivered recently with their newborns was 37.5% (95% CI: 32.6 to 42.6). Factors associated with the utilisation of CBNC included women who attended elementary school (AOR: 1.76, 95% CI: 1.01 to 3.07), college and above (AOR: 3.71, 95% CI: 1.12 to 12.24), farmer women (AOR: 0.35, 95% CI: 0.16 to 0.79), women in the lowest (AOR: 3.76, 95% CI: 1.65 to 8.54) and middle quantile of wealth status (AOR: 1.96, 95% CI: 1.01 to 3.76), and those whose preference was visiting hospital only when they faced any signs of danger (AOR: 0.29, 95% CI: 0.11 to 0.78). Conclusion: The use of the CBNC programme in the study area was surprisingly low. To increase utilisation and potentially improve the outcomes of these neonates, we need to increase awareness at community levels, make convenient arrangements and increase the availability of services at nearby health facilities that are essential to improve the uptake of CBNC in the rural district.